The Neuropsychological Profile of Mild Cognitive Impairment in Lewy Body Dementias. (12th December 2019) - Ciafone, Joanna; Little, Bethany; Thomas, Alan J.; Gallagher, Peter
Abstract: Objectives: Dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD) have substantial clinical and biological overlap, with cognitive deficits typically observed in the executive and visuospatial domains. However, the neuropsychological profiles of mild cognitive impairment (MCI) associated with these disorders are not well understood. Methods: This systematic review examined existing literature on cognition in MCI due to LB disease (MCI-LB) and PD (PD-MCI) using an electronic search of seven databases (Medline, Embase, Psychinfo, PubMed, ProQuest, Scopus, and ScienceDirect). MCI-LB results were reviewed narratively given the small number of resulting papers ( n = 7). Outcome variables from PD-MCI studies ( n = 13) were extracted for meta-analysis of standardised mean differences (SMD). Results: In MCI-LB, executive dysfunction and slowed processing speed were the most prominent impairments, while visuospatial and working memory (WM) functions were also poor. MCI-LB scored significantly lower on verbal memory tests relative to controls, but significantly higher than patients with MCI due to Alzheimer's disease. Quantitative analysis of studies in PD-MCI showed a similar profile of impairment, with the largest deficits in visuospatial function (Benton Judgement of Line Orientation, SMD g = −2.09), executive function (Trail Making Test B, SMD g = −1.65), verbal ability (Naming Tests, SMD g = −0.140), and WM (Trail Making Test A, SMD g = −1.20). In both MCI-LB and PD-MCI, verbal and visuospatial memory retrieval was impaired, while encoding and storage appeared relatively intact. Conclusions: The findings of this systematic review indicate similar neuropsychological profiles in the MCI stages of DLB and PDD. Executive impairment may at least partially explain poor performance in other domains.